2016
DOI: 10.1017/asr.2016.84
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Wealth and Protest in Sub-Saharan Africa

Abstract: Abstract:Challenging the scholarship on the relationship between natural resources and civil society, this article advances a framework that differentiates the various types of protests surrounding mineral extraction in sub-Saharan Africa and explains how this extraction encourages contentious activity. On the basis of protest event data from thirty-nine countries in SSA for the 1990–2006 period, as well as available survey data, the article provides confirming evidence that mineral wealth increases protest ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…168 Arce and Miller note that while some groups do protest the Ahafo mine because of its environmental impacts-including the cyanide spill of October 2009 169 -those Ahafo community members who are benefiting from the mine are not opposed to the mine or protesting for closure but are rather raising grievances concerning the need for better use of finances, respect for rights, and distribution of services. 170 This is in contrast to many Latin American contexts, where protests have galvanized into strong anti-mining movements.…”
Section: Independent Findingsmentioning
confidence: 94%
See 1 more Smart Citation
“…168 Arce and Miller note that while some groups do protest the Ahafo mine because of its environmental impacts-including the cyanide spill of October 2009 169 -those Ahafo community members who are benefiting from the mine are not opposed to the mine or protesting for closure but are rather raising grievances concerning the need for better use of finances, respect for rights, and distribution of services. 170 This is in contrast to many Latin American contexts, where protests have galvanized into strong anti-mining movements.…”
Section: Independent Findingsmentioning
confidence: 94%
“…Second, concerns over land expropriation, water rights, and environmental contamination have resulted in many community protests opposing the mine. 158 Third, there are insufficient property rights protections in Ghana. 159 In terms of net impact, Ghanaian researchers Lawson and Bentil surveyed two communities affected by the Ahafo mine (and BAs) and found that self-reported satisfaction with public service as well as income and appraisal of the economic situation had, if anything, gotten worse since the mine's inception in 2006.…”
Section: Independent Findingsmentioning
confidence: 99%
“…Gudrun Østby et al (2009) note that relative deprivation mixed with extractible commodities make a region significantly more prone to armed conflict. Moisés Arce and Rebecca Miller (2016) conclude that in Kenya the extractive industry is leading to protests over benefits sharing, livelihoods, and environmental issues, and that "participation deficits" can result, disengaging citizens from the state. This, they say, will continue to increase as the state fails to act to ensure a fair distribution of the benefits of increased developmental activity in marginal areas.…”
Section: Dynamic Dispossession and The New Dynamics Of Conflictmentioning
confidence: 99%
“…Much of the existing literature examines the variation of resource conflicts cross-nationally (Arce & Miller, 2016;Arce et al, 2018;Haslam & Tanimoune, 2015) and sub-nationally (Arce & Hendricks, 2019;Arellano-Yanguas, 2010;Mähler & Pierskalla, 2015;Ponce & McClintock, 2014;Orihuela et al, 2019). Some studies examine the relationship between mineral wealth and conflicts (Arce & Hendricks, 2019;Arellano-Yanguas, 2010).…”
Section: Introductionmentioning
confidence: 99%